Implikasi Penggunaan Teknologi Informasi dan Komunikasi (TIK) terhadap Aspek Sosial Budaya Masyarakatdi Kabupaten Mimika - Emilsyah Nur (Journal of Communication Sciences (JCoS), 2019)
This study was conducted to determine the understanding and use of ICT in households selected as respondents in the Mimika Regency, Papua Province. This research uses FGD by inviting several experts. The results of this study indicatet hat the level of understanding and use of ICT among the community in the Mimika Regency of Papua Province has not been maximized due to several obstacles such as: Uneven network infrastructure in the area, signals that have not been maximized in providing information needed by local communities, and the role of the Government Local areas that are still less responsive to ICT problems in the area. As a result, there has been a shift in thesocio-cultural implications of  the community in Mimika Regency, Papua Province.